POLITICAS DE JUVENTUDE(S): Os impactos na dimensão política do Proyecto Adolescentes no contexto de um sistema clientelista em Buenos Aires - Ramirez, Graciela Noemí (2011)
This paper investigates the impacts on young people in what concerns their political dimension after their participation in the Proyecto Adolecentes, based on an evaluative study. Specifically, it analyzes and discusses the following: the PA representation, the existence of an expansion of the reference zone, political participation and areas of participation. The program has been developed in the province of Buenos Aires (Argentina) within the period of 2005-2010, and for the purposes of the research one of municipality applying the programme has been defined as the geographic location whereas the year of 2008 (implementation of the project) was defined as the time reference. The work adopts a constructivist sociological perspective in order to avoid the structure - action dichotomy whilst it also makes use of symbolic anthropology when it tries to interpret the speech of young people: a focus in which not only one theory is established but that also bestows importance to the cultural context of the phenomenon under investigation. It is based on a qualitative approach and the main source is the interviews with users of the program. Based on these resources the research presents and analyzes the processes of implementation of the program as well as the meaning that the experience as a PA user acquires to the youngsters. It evaluates the impacts in their ways of conceiving and practicing politics, the political machine system being an important factor for understanding such processes.